ASESSMEN PELAKSANAAN PROJEK PENGUATAN PROFIL PELAJAR PANCASILA (P5) DALAM KURIKULUM MERDEKA DI TK WITRI KOTA BENGKULU - Husna, Nasratul (LPPM Universitas Muhammadiyah Cirebon, 2024)
The Strengthening of Student Pancasila Profile Project is one of the most crucial elements in the Merdeka Curriculum. This project involves a planning process consisting of several steps, including the appointment of facilitator teams, evaluation of the readiness level of educational units, designing dimensions, themes, and time allocation, compiling project modules, and designing strategies for reporting project results. The aim of this research is to investigate the implementation of the Strengthening of Student Pancasila Profile Project in Early Childhood Education (ECE) institutions. This research adopts a qualitative approach with data collection techniques including observation, interviews, and documentation to elucidate how this project is implemented as part of the Merdeka Curriculum in ECE institutions. The data analysis method employed is the interactive model by Miles and Huberman, comprising data collection, data reduction, data presentation, and conclusion drawing. The research findings indicate that educational units have followed the established planning process and adapted it to their circumstances, including selecting one theme from P5. In conclusion, ECE institutions in Serang City have successfully implemented P5 by designing its themes and topics, creating project modules, and implementing them in their institutions